THE FEATURES OF FATTY ACIDS IN CYANOBACTERIAL MATS FROM THE MCMURDO DRY VALLEYS REGION, ANTARCTICA (ABSTRACT) (14th Symposium on Polar Biology) - ヒロタ, コウイツ; マツモト, ゲンキ; オオタニ, シュウジ; HIROTA, Koitsu; MATSUMOTO, Genki I.; OHTANI, Shuji (National Institute of Polar Research, 1993)
P(論文) departmental bulletin paper